Tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, preparation method and application thereof

Through the coordinated flame retardant mechanism of tin bismuth-based high-efficiency flame retardant and surfactant modification, the problems of unstable performance and environmental pollution in coal mine environments are solved, and the flame retardant effect with high efficiency, environmental protection and excellent mechanical properties are achieved.

CN118994724BActive Publication Date: 2025-04-18SHANDONG HONGAN NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411110564.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-04-18
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The flame retardant of non-metal products in existing coal mines has problems such as large amounts of added, unstable flame retardant performance, environmental pollution and mechanical properties, and it is difficult to provide long-term safety guarantees in complex coal mine environments.

Method used

A tin-bismuth-based high-efficiency flame retardant is used. The flame retardant is combined with antimony trioxide, zinc borate, calcium hydroxyphosphate and other components to form a synergistic flame retardant effect, and is modified by silane coupling agents and other surfactants to improve dispersion and stability.

Benefits of technology

It significantly improves the flame retardant performance and mechanical properties of non-metal products in coal mines, has good environmental friendliness and smoke suppression, and is suitable for long-term use in complex coal mine environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, and a preparation method and application thereof, and relates to the field of non-metallic products in coal mines. The tin-bismuth-based high-efficiency flame retardant comprises modified tin powder, bismuth powder, antimony trioxide, zinc borate, calcium hydroxyphosphate, ammonium polyphosphate, nano silicon dioxide, magnesium oxide, aluminum hydroxide, silane coupling agent, octylphenol polyoxyethylene ether and polyvinyl pyrrolidone. The main components of the tin-bismuth-based high-efficiency flame retardant, tin powder and bismuth powder, can react rapidly at high temperature to form a flame retardant layer, prevent the spread of combustion, and improve the fireproof ability of non-metallic products in coal mines. The surface of the modified tin powder is coated with an aluminum oxide layer to improve the heat resistance and flame retardant effect. Zinc borate and calcium hydroxyphosphate are added to decompose at high temperature to generate water vapor and phosphoric acid, effectively dilute the smoke generated by combustion, and form a carbonized protective film at the same time, further reduce the emission of smoke, improve the safety of the product, and have a high-efficiency flame retardant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coal mine non-metallic products, and in particular to a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products, and a preparation method and application thereof. Background Art

[0002] Coal mine non-metallic products, such as pipes, seals and cable sheaths, have important applications in coal mine environments. However, due to the particularity of the coal mine environment, these non-metallic products face multiple tests such as high temperature, flammable substances and mechanical stress during use. In order to ensure the safe production and operation of coal mines, non-metallic products must have excellent flame retardant properties.

[0003] In the existing technology, the flame retardant properties of non-metallic products in coal mines mainly rely on the addition of various flame retardants. However, traditional flame retardants have the following shortcomings:

[0004] 1. Large amount of addition: In order to achieve the ideal flame retardant effect, traditional flame retardants need to be added in large quantities, which not only increases the cost of the product, but may also affect the mechanical properties and processing properties of the material.

[0005] 2. Unstable flame retardant performance: Some flame retardants are prone to decomposition or failure under high temperature conditions, resulting in unstable flame retardant properties of the material and unable to guarantee the safe use of the product in the long term.

[0006] 3. Environmental pollution issues: Some traditional flame retardants contain halogens or other harmful chemical components, which may release toxic gases or residues during use and disposal, posing a potential threat to the environment and human health.

[0007] 4. Impact on mechanical properties: Many flame retardants, while improving flame retardancy, often have an adverse effect on the mechanical properties of materials (such as tensile strength, toughness, etc.), making the products prone to breakage or aging in actual use.

[0008] In response to the above problems, how to develop a flame retardant that is efficient, environmentally friendly, has excellent mechanical properties and is easy to industrialize has become an important research direction in the field of coal mine non-metallic products. Summary of the invention

[0009] In view of this, the present invention aims to provide a tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, and a preparation method and application thereof. The flame retardant combines tin-based and bismuth-based compounds to configure a tin-bismuth-based flame retardant with high-efficiency flame retardant effect. At the same time, it is halogen-free and environmentally friendly, so that its application prospect in non-metallic products in coal mines is broader. It not only significantly improves the flame retardant properties of non-metallic products, but also has good mechanical properties and environmental friendliness, and is suitable for use in the complex environment of coal mines.

[0010] To achieve the above object, the present invention provides the following technical solutions:

[0011] In a first aspect, the present invention provides a tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, comprising the following raw materials in parts by weight:

[0012] 40-60 parts of modified tin powder; 20-30 parts of bismuth powder; 5-10 parts of antimony trioxide; 5-10 parts of zinc borate; 2-4 parts of calcium hydroxyphosphate; 3-6 parts of ammonium polyphosphate; 1-3 parts of nano silicon dioxide; 2-5 parts of magnesium oxide; 10-20 parts of aluminum hydroxide; 0.5-1 parts of silane coupling agent; 0.1-0.5 parts of octylphenol polyoxyethylene ether and 0.2-0.6 parts of polyvinyl pyrrolidone.

[0013] As a further solution of the present invention, the modified tin powder is tin powder with alumina coated on the surface, the particle size of the modified tin powder is 10-50um, the thickness of the alumina coating layer is 100nm, the loose density is 2.0-2.5 g / cm³, and the modified tin powder forms a uniform alumina coating layer on the surface of the tin powder by chemical vapor deposition.

[0014] As a further solution of the present invention, the bismuth powder has a particle size of 10-50 um and a bulk density of 9.8-10.2 g / cm³, and is used to combine with modified tin powder to form a tin-bismuth alloy.

[0015] As a further solution of the present invention, the zinc borate is an ultrafine zinc borate with a particle size of 50-100nm and a specific surface area of ​​30m² / g; the hydroxy calcium phosphate is a nano hydroxy calcium phosphate with a particle size of 20-50nm and a specific surface area of ​​60m² / g, which is used to synergistically flame retardant with zinc borate. When zinc borate decomposes water vapor at high temperature, water vapor and phosphoric acid decomposed by hydroxy calcium phosphate at high temperature play a smoke suppression effect by synergistically releasing water vapor to dilute the smoke generated by combustion and promote the formation of a carbon layer.

[0016] As a further solution of the present invention, the particle size of the antimony trioxide is 100nm to 1um, and the specific surface area is 20m² / g; the particle size of the ammonium polyphosphate is 100-500nm, the density is 1.9g / cm³, and the degree of polymerization of the ammonium polyphosphate is greater than 200, which is used to cooperate with micro-nano antimony trioxide.

[0017] As a further solution of the present invention, the particle sizes of the nano-silicon dioxide, magnesium oxide and aluminum hydroxide are all between 10-50 nm, wherein the specific surface area of ​​the nano-silicon dioxide is 200-400 m² / g, the specific surface area of ​​the magnesium oxide is 150 m² / g, and the specific surface area of ​​the aluminum hydroxide is 100 m² / g, and the magnesium oxide is used to act synergistically with the aluminum hydroxide and the nano-silicon dioxide.

[0018] As a further solution of the present invention, the silane coupling agent is γ-aminopropyltriethoxysilane, which is used to chemically react with the surface of nano-silicon dioxide through the silane group, chemically react with the surface of magnesium oxide through the amino group, and chemically react with the surface of aluminum hydroxide through the organic group, so as to modify the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide.

[0019] As a further scheme of the present invention, the octylphenol polyoxyethylene ether is used as an emulsifier to form a stable emulsion between the oil phase and the water phase, and is used to disperse the solid particles of the modified tin powder and bismuth powder. It is prepared by reacting octylphenol and ethylene oxide in a reactor through nitrogen replacement and adding potassium hydroxide as a catalyst. During the reaction, the temperature is raised to 130-150°C, ethylene oxide is gradually added, and the reaction pressure is maintained between 0.2-0.4 MPa. The reaction is carried out for 3-6 hours until the ethylene oxide and octylphenol react completely. The target product is subjected to reduced pressure distillation to remove unreacted ethylene oxide and volatile substances, and then the octylphenol polyoxyethylene ether is purified and dried.

[0020] As a further solution of the present invention, the polyvinyl pyrrolidone is K30 type polyvinyl pyrrolidone with a viscosity of 5-10 mPa.s and a density of 1.2 g / cm³. Vinyl pyrrolidone monomer and potassium persulfate are reacted by adding ethanol into a reaction container, the reaction temperature is controlled between 60-80°C, the reaction is stirred evenly for 4-8 hours, and the polyvinyl pyrrolidone is separated and used for synergistic effect with octylphenol polyoxyethylene ether.

[0021] In a second aspect, the present invention also provides a method for preparing a tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, the steps being as follows:

[0022] 1) Weigh modified tin powder, bismuth powder, antimony trioxide, zinc borate, calcium hydroxyphosphate, ammonium polyphosphate, nano silicon dioxide, magnesium oxide, aluminum hydroxide, silane coupling agent, octylphenol polyoxyethylene ether and polyvinyl pyrrolidone according to weight parts and set aside;

[0023] 2) Activation treatment of bismuth powder: dissolving 20% ​​of the weighed silane coupling agent in anhydrous ethanol to prepare a 0.5-1% silane coupling agent solution; spreading the bismuth powder evenly, and spraying the silane coupling agent solution on the surface of the spread bismuth powder, placing the sprayed bismuth powder in an oven, and drying it at 80-100° C. for 1-2 hours to obtain bismuth powder activated by the silane coupling agent;

[0024] 3) adding the modified tin powder and the activated bismuth powder into a ball mill according to a weight ratio for pre-mixing by ball milling to form a tin-bismuth alloy powder;

[0025] 4) Add nano-silicon dioxide, magnesium oxide and aluminum hydroxide into the reactor, and slowly add the remaining amount of silane coupling agent, with a stirring speed of 200-250 r / min, a stirring time of 10-20 minutes, and a temperature of 25°C, so that the silane coupling agent fully reacts with the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide to perform surface modification;

[0026] 5) Antimony trioxide, zinc borate, calcium hydroxyphosphate and ammonium polyphosphate are added to the reactor, and stirring is continued for 5-10 minutes at 300-500 r / min to obtain a mixed flame retardant component, and the tin-bismuth alloy powder formed in the ball mill is transferred to the reactor, and stirring is continued for 15-30 minutes until the components are evenly mixed to obtain a reinforced mixture;

[0027] 6) Octylphenol polyoxyethylene ether and polyvinyl pyrrolidone are mixed according to a ratio, and the formed emulsion is added to the reinforced mixture in the reactor, and mixed at a speed of 300-500 r / min for 30-60 minutes, so that the emulsion fully disperses the solid particles of the modified tin powder and bismuth powder to form a flame retardant mixed slurry;

[0028] 7) Dry the mixed slurry to remove moisture, control the drying temperature at 60-80°C, and dry for 3-5 hours. After drying, crush and sieve the material to obtain a tin-bismuth-based high-efficiency flame retardant product with uniform particle size, put it into a sealed container, and store it in a dry and cool place for use.

[0029] As a further embodiment of the present invention, the method for preparing the tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products further includes the preparation of modified tin powder, and the preparation method of the modified tin powder includes the following steps:

[0030] Step 1. Preparation of tin powder: Take tin powder with a particle size of 10-50µm;

[0031] Step 2, Chemical Vapor Deposition (CVD) Reactor Cleaning: Ensure that there are no impurities and contaminants inside the CVD reactor, and spread the tin powder with a particle size of 10-50µm evenly on the reaction platform inside the CVD reactor;

[0032] Step 3, nitrogen flushing: at room temperature, high-purity nitrogen is passed through the reactor for 20-30 minutes to remove air and moisture inside the reactor;

[0033] Step 4, heating: heating the reactor to 300-400°C;

[0034] Step 5, introducing aluminum source compound and oxygen: gasify aluminum trichloride, introduce aluminum trichloride as aluminum source compound, use nitrogen as carrier gas into the reactor, introduce high-purity oxygen as oxidant, control the oxygen flow rate, and react for 30-60 minutes;

[0035] Step 6, cooling and flushing: turn off the supply of aluminum chloride and oxygen reaction gas, continue to introduce high-purity nitrogen, and slowly cool down to room temperature;

[0036] Step 7, collecting modified tin powder: open the reactor, take out the sample tray, and sieve to collect the modified tin powder with a particle size of 10-50µm.

[0037] As a further scheme of the present invention, during the activation treatment of the bismuth powder, bismuth powder with a particle size of 10-50 μm is taken, the bismuth powder is evenly spread, the sprayer is kept at a distance of 20-30 cm from the surface of the bismuth powder to spray the silane coupling agent solution, the bismuth powder is stirred several times with a stirrer and the silane coupling agent solution is evenly sprayed again, the sprayed bismuth powder is placed in an oven, and dried at 80-100° C. for 1-2 hours to obtain bismuth powder activated by the silane coupling agent.

[0038] As a further scheme of the present invention, during the activation treatment of nano-silicon dioxide, nano-silicon dioxide with a particle size of 10-50 nm is taken, the nano-silicon dioxide is evenly spread, a silane coupling agent solution is sprayed on the surface of the nano-silicon dioxide, the nano-silicon dioxide is stirred several times with a stirrer and the silane coupling agent solution is evenly sprayed again, the sprayed nano-silicon dioxide is placed in an oven, and dried at 80-100° C. for 1-2 hours to obtain nano-silicon dioxide activated by a silane coupling agent.

[0039] In a third aspect, the present invention further provides a non-metallic coal mine product, which is manufactured using a tin-bismuth-based high-efficiency flame retardant for non-metallic coal mine products. The manufacturing method of the non-metallic coal mine product is:

[0040] The prepared tin-bismuth-based high-efficiency flame retardant powder is evenly added to the base material at a mass ratio of 5-10%, the flame retardant and the base material are fully mixed by a high-speed mixer, and the mixed material is processed into the required coal mine non-metallic products by injection molding, extrusion or compression molding.

[0041] Compared with the prior art, the tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products of the present invention and its preparation method and application have the following beneficial effects:

[0042] 1. Excellent flame retardant performance: This tin-bismuth-based flame retardant can effectively inhibit combustion under high temperature conditions. Its main components, tin powder and bismuth powder, can react quickly at high temperatures to form a flame retardant layer to prevent the spread of combustion and improve the fire resistance of non-metallic products in coal mines. The surface of the modified tin powder is coated with an alumina layer to improve the heat resistance and flame retardant effect. The optimization of particle size and bulk density ensures its uniform distribution in the mixture.

[0043] 2. It has a highly effective smoke suppression effect: Due to the addition of zinc borate and calcium hydroxyphosphate, it decomposes at high temperature to generate water vapor and phosphoric acid, which effectively dilutes the smoke produced by combustion and forms a carbonized protective film, further reducing smoke emissions and improving product safety.

[0044] 3. Synergistic flame retardant effect: The synergistic effect between antimony trioxide, ammonium polyphosphate, nano-silicon dioxide, magnesium oxide and aluminum hydroxide in the tin-bismuth-based flame retardant significantly enhances the overall performance of the flame retardant. Antimony trioxide and ammonium polyphosphate work together to promote the formation of a stable flame retardant structure; nano-silicon dioxide and magnesium oxide improve the dispersion and uniformity of the material, further enhancing the flame retardant effect.

[0045] 4. Surface modification improves performance: In the tin-bismuth-based flame retardant, the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide is modified by the silane coupling agent γ-aminopropyltriethoxysilane, which improves their compatibility and dispersibility with other components and ensures the uniform distribution and stability of the flame retardant.

[0046] 5. Efficient and easy-to-use preparation method: The flame retardant preparation method of the present invention is simple and easy. Through the steps of proportioning and chemical vapor deposition, mixing, emulsification, drying and molding, the efficient mixer and emulsification treatment ensure the full mixing and dispersion of the components, improve the uniformity and stability of the flame retardant, ensure the high efficiency and consistency of the product, and are suitable for large-scale industrial production. All raw materials are non-toxic and harmless materials, meet environmental protection standards, and will not pollute the environment. In particular, environmentally friendly flame retardant ingredients such as modified tin powder and bismuth powder are selected to reduce the release of harmful substances and protect the environment and human health; the flame retardant is suitable for a variety of non-metallic products in coal mines, such as cable sheaths, plastic products, rubber products, etc., which improves the fire resistance and safety of these products and provides strong technical support for safe production in coal mines.

[0047] In summary, the tin-bismuth-based high-efficiency flame retardant of the present invention and its preparation method and application have the advantages of excellent flame retardant properties, efficient smoke suppression, significant synergistic effect, environmental friendliness, etc., are suitable for wide application in non-metallic products in coal mines, improve the safety and reliability of coal mine production, and provide a new solution for fire protection technology.

[0048] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods. Example 1

[0050] This embodiment provides a tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, comprising the following raw materials in parts by weight:

[0051] 40 parts of modified tin powder; 20 parts of bismuth powder; 5 parts of antimony trioxide; 5 parts of zinc borate; 2 parts of calcium hydroxyphosphate; 3 parts of ammonium polyphosphate; 1 part of nano silicon dioxide; 2 parts of magnesium oxide; 10 parts of aluminum hydroxide; 0.5 parts of silane coupling agent; 0.1 parts of octylphenol polyoxyethylene ether, and 0.2 parts of polyvinyl pyrrolidone.

[0052] In this embodiment, the modified tin powder is tin powder with aluminum oxide coated on the surface. The particle size of the modified tin powder is 30±10um, the thickness of the aluminum oxide coating layer is 100nm, and the bulk density is 2.3 g / cm³. The modified tin powder forms a uniform aluminum oxide coating layer on the surface of the tin powder by chemical vapor deposition.

[0053] The bismuth powder has a particle size of 25±10um and a bulk density of 10 g / cm³, and is used to combine with modified tin powder to form a tin-bismuth alloy; the zinc borate is an ultrafine zinc borate with a particle size of 75±10nm and a specific surface area of ​​30m² / g; the hydroxy calcium phosphate is a nano hydroxy calcium phosphate with a particle size of 35±10nm and a specific surface area of ​​60m² / g, and is used to synergistically flame retardant with zinc borate. When zinc borate decomposes water vapor at high temperature, water vapor and phosphoric acid decomposed by hydroxy calcium phosphate at high temperature play a smoke suppression role by synergistically releasing water vapor to dilute the smoke generated by combustion and promote the formation of a carbon layer.

[0054] The particle size of antimony trioxide is 500±100nm, and the specific surface area is 20m² / g; the particle size of ammonium polyphosphate is 300±100nm, and the density is 1.9g / cm³. The degree of polymerization of ammonium polyphosphate is greater than 200, and it is used to cooperate with micro-nano antimony trioxide. The particle sizes of nano silicon dioxide, magnesium oxide and aluminum hydroxide are all 30±10nm, and the specific surface area of ​​nano silicon dioxide is 300 m² / g, the specific surface area of ​​magnesium oxide is 150 m² / g, and the specific surface area of ​​aluminum hydroxide is 100 m² / g. Magnesium oxide is used to cooperate with aluminum hydroxide and nano silicon dioxide.

[0055] In this embodiment, the silane coupling agent is γ-aminopropyltriethoxysilane, which is used to chemically react with the surface of nano-silicon dioxide through the silane group, chemically react with the surface of magnesium oxide through the amino group, and chemically react with the surface of aluminum hydroxide through the organic group, thereby modifying the surface of nano-silicon dioxide, magnesium oxide, and aluminum hydroxide.

[0056] The octylphenol polyoxyethylene ether is used as an emulsifier to form a stable emulsion between the oil phase and the water phase, and is used to disperse the solid particles of modified tin powder and bismuth powder. It is prepared by nitrogen replacement of octylphenol and ethylene oxide in a reactor, and potassium hydroxide is added as a catalyst. During the reaction, the temperature is raised to 140°C, ethylene oxide is gradually added, and the reaction pressure is maintained between 0.23 MPa. The reaction is carried out for 5 hours until ethylene oxide and octylphenol are completely reacted. The target product is subjected to reduced pressure distillation to remove unreacted ethylene oxide and volatile substances, and then the octylphenol polyoxyethylene ether is purified and dried.

[0057] The polyvinyl pyrrolidone is K30 type polyvinyl pyrrolidone with a viscosity of 8 mPa.s and a density of 1.2 g / cm³. Vinyl pyrrolidone monomer and potassium persulfate are reacted by adding ethanol into a reaction container, the reaction temperature is controlled between 70°C, the reaction is carried out after stirring evenly for 6 hours, and the polyvinyl pyrrolidone is separated and used for synergistic effect with octylphenol polyoxyethylene ether.

[0058] The preparation method of the tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products in this embodiment comprises the following steps:

[0059] 1) Weigh modified tin powder, bismuth powder, antimony trioxide, zinc borate, calcium hydroxyphosphate, ammonium polyphosphate, nano silicon dioxide, magnesium oxide, aluminum hydroxide, silane coupling agent, octylphenol polyoxyethylene ether and polyvinyl pyrrolidone according to weight parts and set aside;

[0060] 2) Activation treatment of bismuth powder: dissolving 20% ​​of the weighed silane coupling agent in anhydrous ethanol to prepare a 0.75% silane coupling agent solution; spreading the bismuth powder evenly, and spraying the silane coupling agent solution on the surface of the spread bismuth powder, placing the sprayed bismuth powder in an oven, and drying it at 90° C. for 1.5 hours to obtain bismuth powder activated by the silane coupling agent;

[0061] 3) adding the modified tin powder and the activated bismuth powder into a ball mill according to a weight ratio for pre-mixing by ball milling to form a tin-bismuth alloy powder;

[0062] 4) Add nano-silicon dioxide, magnesium oxide and aluminum hydroxide into the reactor, and slowly add the remaining amount of silane coupling agent, with a stirring speed of 250 r / min and a stirring time of 10 minutes. The temperature is controlled at 25°C to allow the silane coupling agent to fully react with the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide for surface modification;

[0063] 5) Antimony trioxide, zinc borate, calcium hydroxyphosphate and ammonium polyphosphate were added to the reactor, and stirring was continued at 400 r / min for 8 minutes to obtain a mixed flame retardant component, and the tin-bismuth alloy powder formed in the ball mill was transferred to the reactor, and stirring was continued for 25 minutes until the components were uniformly mixed to obtain a reinforced mixture;

[0064] 6) Octylphenol polyoxyethylene ether and polyvinyl pyrrolidone are mixed according to a ratio, and the formed emulsion is added to the reinforced mixture in the reactor, and mixed at a speed of 400 r / min for 45 minutes. The emulsion fully disperses the solid particles of the modified tin powder and bismuth powder to form a flame retardant mixed slurry;

[0065] 7) Dry the mixed slurry to remove moisture. The drying temperature is controlled at 70°C and the drying time is 4 hours. After drying, the material is crushed and sieved to obtain a tin-bismuth-based high-efficiency flame retardant product with uniform particle size. The finished product is packed into a sealed container and stored in a dry and cool place for use.

[0066] The present invention also provides a coal mine non-metallic product, which is manufactured using a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products. The manufacturing method of the coal mine non-metallic product is as follows: uniformly adding the prepared tin-bismuth-based high-efficiency flame retardant powder to 95% polypropylene (PP) at a mass ratio of 5%, weighing 5% of the tin-bismuth-based high-efficiency flame retardant and 95% of the polypropylene (PP) matrix material according to the mass ratio, and uniformly adding the tin-bismuth-based high-efficiency flame retardant powder to the polypropylene (PP); using a high-speed mixer to fully mix at a speed of 2000 r / min for 20 minutes to fully mix the flame retardant and the matrix material, and subjecting the uniformly mixed material to an injection molding process, injection molding at 200°C, a molding pressure of 100 MPa, and cooling to obtain a coal mine non-metallic product with excellent flame retardant properties. Example 2

[0067] Different from Example 1, this example provides a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products, comprising the following raw materials in parts by weight:

[0068] 45 parts of modified tin powder; 23 parts of bismuth powder; 6 parts of antimony trioxide; 6 parts of zinc borate; 2.5 parts of calcium hydroxyphosphate; 4 parts of ammonium polyphosphate; 1.5 parts of nano silicon dioxide; 3 parts of magnesium oxide; 13 parts of aluminum hydroxide; 0.6 parts of silane coupling agent; 0.2 parts of octylphenol polyoxyethylene ether, and 0.3 parts of polyvinyl pyrrolidone.

[0069] The preparation method of the tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products in this embodiment comprises the following steps:

[0070] 1) Weigh modified tin powder, bismuth powder, antimony trioxide, zinc borate, calcium hydroxyphosphate, ammonium polyphosphate, nano silicon dioxide, magnesium oxide, aluminum hydroxide, silane coupling agent, octylphenol polyoxyethylene ether and polyvinyl pyrrolidone according to weight parts and set aside;

[0071] 2) Activation treatment of bismuth powder: dissolving 20% ​​of the weighed silane coupling agent in anhydrous ethanol to prepare a 1% silane coupling agent solution; spreading the bismuth powder evenly, and spraying the silane coupling agent solution on the surface of the spread bismuth powder, placing the sprayed bismuth powder in an oven, and drying it at 100° C. for 1 hour to obtain bismuth powder activated by the silane coupling agent;

[0072] 3) adding the modified tin powder and the activated bismuth powder into a ball mill according to a weight ratio for pre-mixing by ball milling to form a tin-bismuth alloy powder;

[0073] 4) Add nano-silicon dioxide, magnesium oxide and aluminum hydroxide into the reactor, and slowly add the remaining amount of silane coupling agent, with a stirring speed of 200 r / min and a stirring time of 20 minutes. The temperature is controlled at 25°C to allow the silane coupling agent to fully react with the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide for surface modification;

[0074] 5) Antimony trioxide, zinc borate, calcium hydroxyphosphate and ammonium polyphosphate were added to the reactor, and the mixture was stirred at 300 r / min for 10 minutes to obtain a mixed flame retardant component. The tin-bismuth alloy powder formed in the ball mill was transferred to the reactor, and the mixture was stirred for 30 minutes until the components were evenly mixed to obtain a reinforced mixture.

[0075] 6) Octylphenol polyoxyethylene ether and polyvinyl pyrrolidone are mixed according to a ratio, and the formed emulsion is added to the reinforced mixture in the reactor, and mixed at a speed of 500 r / min for 30 minutes. The emulsion fully disperses the solid particles of the modified tin powder and bismuth powder to form a flame retardant mixed slurry;

[0076] 7) Dry the mixed slurry to remove moisture. The drying temperature is controlled at 80°C and the drying time is 4 hours. After drying, the material is crushed and sieved to obtain a tin-bismuth-based high-efficiency flame retardant product with uniform particle size. The finished product is packed into a sealed container and stored in a dry and cool place for use.

[0077] The present invention also provides a coal mine non-metallic product, which is manufactured based on a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products. The manufacturing method of the coal mine non-metallic product is as follows: the prepared tin-bismuth-based high-efficiency flame retardant powder is uniformly added to 93% polyvinyl chloride (PVC) at a mass ratio of 7%, 7% of the tin-bismuth-based high-efficiency flame retardant and 93% of the polyvinyl chloride (PVC) matrix material are weighed according to the mass ratio, the tin-bismuth-based high-efficiency flame retardant powder is uniformly added to the polyvinyl chloride (PVC), and a high-speed mixer is used to fully mix at a speed of 1800 r / min for 25 minutes to fully mix the flame retardant and the matrix material, and the uniformly mixed material is subjected to an extrusion process to be extruded at 160°C, and the extrusion pressure is 80 MPa; after cooling, a coal mine non-metallic product with excellent flame retardant properties is obtained. Example 3

[0078] Different from Example 1, this example provides a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products, comprising the following raw materials in parts by weight:

[0079] 50 parts of modified tin powder; 25 parts of bismuth powder; 7.5 parts of antimony trioxide; 7.5 parts of zinc borate; 3 parts of calcium hydroxyphosphate; 4.5 parts of ammonium polyphosphate; 2 parts of nano silicon dioxide; 3.5 parts of magnesium oxide; 15 parts of aluminum hydroxide; 0.75 parts of silane coupling agent; 0.3 parts of octylphenol polyoxyethylene ether, and 0.4 parts of polyvinyl pyrrolidone.

[0080] The preparation method of the tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products in this embodiment comprises the following steps:

[0081] 1) Weigh modified tin powder, bismuth powder, antimony trioxide, zinc borate, calcium hydroxyphosphate, ammonium polyphosphate, nano silicon dioxide, magnesium oxide, aluminum hydroxide, silane coupling agent, octylphenol polyoxyethylene ether and polyvinyl pyrrolidone according to weight parts and set aside;

[0082] 2) Activation treatment of bismuth powder: dissolving 20% ​​of the weighed silane coupling agent in anhydrous ethanol to prepare a 0.7% silane coupling agent solution; spreading the bismuth powder evenly, and spraying the silane coupling agent solution on the surface of the spread bismuth powder, placing the sprayed bismuth powder in an oven, and drying it at 90° C. for 2 hours to obtain bismuth powder activated by the silane coupling agent;

[0083] 3) adding the modified tin powder and the activated bismuth powder into a ball mill according to a weight ratio for pre-mixing by ball milling to form a tin-bismuth alloy powder;

[0084] 4) Add nano-silicon dioxide, magnesium oxide and aluminum hydroxide into the reactor, and slowly add the remaining amount of silane coupling agent, with a stirring speed of 250 r / min and a stirring time of 10 minutes. The temperature is controlled at 25°C to allow the silane coupling agent to fully react with the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide for surface modification;

[0085] 5) Antimony trioxide, zinc borate, calcium hydroxyphosphate and ammonium polyphosphate were added to the reactor, and stirring was continued at 400 r / min for 8 minutes to obtain a mixed flame retardant component, and the tin-bismuth alloy powder formed in the ball mill was transferred to the reactor, and stirring was continued for 25 minutes until the components were uniformly mixed to obtain a reinforced mixture;

[0086] 6) Octylphenol polyoxyethylene ether and polyvinyl pyrrolidone are mixed according to a ratio, and the formed emulsion is added to the reinforced mixture in the reactor, and mixed at a speed of 400 r / min for 45 minutes. The emulsion fully disperses the solid particles of the modified tin powder and bismuth powder to form a flame retardant mixed slurry;

[0087] 7) Dry the mixed slurry to remove moisture. The drying temperature is controlled at 70°C and the drying time is 4 hours. After drying, the material is crushed and sieved to obtain a tin-bismuth-based high-efficiency flame retardant product with uniform particle size. The finished product is packed into a sealed container and stored in a dry and cool place for use.

[0088] The present invention also provides a non-metallic product for coal mines, which is manufactured based on a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products. The manufacturing method of the non-metallic product for coal mines is as follows: the prepared tin-bismuth-based high-efficiency flame retardant powder is uniformly added to 90% polyethylene (PE) at a mass ratio of 10%, and 10% of the tin-bismuth-based high-efficiency flame retardant and 90% of the polyethylene (PE) matrix material are weighed according to the mass ratio. The tin-bismuth-based high-efficiency flame retardant powder is uniformly added to polyethylene (PE); a high-speed mixer is used to fully mix for 30 minutes at a speed of 2200 r / min, so that the flame retardant and the matrix material are fully mixed. The uniformly mixed material is subjected to a molding process, and is molded at 190°C with a molding pressure of 120 MPa. After cooling, a non-metallic product for coal mines with excellent flame retardant properties is obtained. Example 4

[0089] Different from Example 1, this example provides a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products, comprising the following raw materials in parts by weight:

[0090] 55 parts of modified tin powder; 28 parts of bismuth powder; 8 parts of antimony trioxide; 8 parts of zinc borate; 3.5 parts of calcium hydroxyphosphate; 5 parts of ammonium polyphosphate; 2.5 parts of nano silicon dioxide; 4 parts of magnesium oxide; 18 parts of aluminum hydroxide; 0.9 parts of silane coupling agent; 0.4 parts of octylphenol polyoxyethylene ether, and 0.5 parts of polyvinyl pyrrolidone.

[0091] The preparation method of the tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines in this embodiment comprises the following steps:

[0092] 1) Weigh modified tin powder, bismuth powder, antimony trioxide, zinc borate, calcium hydroxyphosphate, ammonium polyphosphate, nano silicon dioxide, magnesium oxide, aluminum hydroxide, silane coupling agent, octylphenol polyoxyethylene ether and polyvinyl pyrrolidone according to weight parts and set aside;

[0093] 2) Activation treatment of bismuth powder: dissolving 20% ​​of the weighed silane coupling agent in anhydrous ethanol to prepare a 1% silane coupling agent solution; spreading the bismuth powder evenly, and spraying the silane coupling agent solution on the surface of the spread bismuth powder, placing the sprayed bismuth powder in an oven, and drying it at 100° C. for 1 hour to obtain bismuth powder activated by the silane coupling agent;

[0094] 3) adding the modified tin powder and the activated bismuth powder into a ball mill according to a weight ratio for pre-mixing by ball milling to form a tin-bismuth alloy powder;

[0095] 4) Add nano-silicon dioxide, magnesium oxide and aluminum hydroxide into the reactor, and slowly add the remaining amount of silane coupling agent, with a stirring speed of 250 r / min and a stirring time of 10 minutes. The temperature is controlled at 25°C to allow the silane coupling agent to fully react with the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide for surface modification;

[0096] 5) Antimony trioxide, zinc borate, calcium hydroxyphosphate and ammonium polyphosphate were added to the reactor, and stirring was continued at 500 r / min for 5 minutes to obtain a mixed flame retardant component, and the tin-bismuth alloy powder formed in the ball mill was transferred to the reactor, and stirring was continued for 30 minutes until the components were uniformly mixed to obtain a reinforced mixture;

[0097] 6) Octylphenol polyoxyethylene ether and polyvinyl pyrrolidone are mixed according to a ratio, and the formed emulsion is added to the reinforced mixture in the reactor, and mixed at a speed of 500 r / min for 30 minutes. The emulsion fully disperses the solid particles of the modified tin powder and bismuth powder to form a flame retardant mixed slurry;

[0098] 7) Dry the mixed slurry to remove moisture. The drying temperature is controlled at 80°C and the drying time is 3 hours. After drying, the material is crushed and sieved to obtain a tin-bismuth-based high-efficiency flame retardant product with uniform particle size. The finished product is packed into a sealed container and stored in a dry and cool place for use.

[0099] The present invention also provides a non-metallic product for coal mines, which is manufactured based on a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products. The manufacturing method of the non-metallic product for coal mines is as follows: the prepared tin-bismuth-based high-efficiency flame retardant powder is uniformly added to 94% nylon (PA) at a mass ratio of 6%, 6% of the tin-bismuth-based high-efficiency flame retardant and 94% of the nylon (PA) matrix material are weighed according to the mass ratio; the tin-bismuth-based high-efficiency flame retardant powder is uniformly added to the nylon (PA); a high-speed mixer is used to fully mix at a speed of 2500 r / min for 15 minutes to fully mix the flame retardant and the matrix material. The uniformly mixed material is subjected to an injection molding process, and injection molding is performed at 210°C, and the molding pressure is 110 MPa; after cooling, a non-metallic product for coal mines with excellent flame retardant properties is obtained. Example 5

[0100] Different from Example 1, this example provides a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products, comprising the following raw materials in parts by weight:

[0101] 60 parts of modified tin powder; 30 parts of bismuth powder; 10 parts of antimony trioxide; 10 parts of zinc borate; 4 parts of calcium hydroxyphosphate; 6 parts of ammonium polyphosphate; 3 parts of nano silicon dioxide; 5 parts of magnesium oxide; 20 parts of aluminum hydroxide; 1 part of silane coupling agent; 0.5 parts of octylphenol polyoxyethylene ether and 0.6 parts of polyvinyl pyrrolidone.

[0102] The preparation method of the tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products in this embodiment comprises the following steps:

[0103] 1) Weigh modified tin powder, bismuth powder, antimony trioxide, zinc borate, calcium hydroxyphosphate, ammonium polyphosphate, nano silicon dioxide, magnesium oxide, aluminum hydroxide, silane coupling agent, octylphenol polyoxyethylene ether and polyvinyl pyrrolidone according to weight parts and set aside;

[0104] 2) Activation treatment of bismuth powder: dissolving 20% ​​of the weighed silane coupling agent in anhydrous ethanol to prepare a 1% silane coupling agent solution; spreading the bismuth powder evenly, and spraying the silane coupling agent solution on the surface of the spread bismuth powder, placing the sprayed bismuth powder in an oven, and drying it at 100° C. for 1 hour to obtain bismuth powder activated by the silane coupling agent;

[0105] 3) adding the modified tin powder and the activated bismuth powder into a ball mill according to a weight ratio for pre-mixing by ball milling to form a tin-bismuth alloy powder;

[0106] 4) Add nano-silicon dioxide, magnesium oxide and aluminum hydroxide into the reactor, and slowly add the remaining amount of silane coupling agent, with a stirring speed of 200 r / min and a stirring time of 20 minutes. The temperature is controlled at 25°C to allow the silane coupling agent to fully react with the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide for surface modification;

[0107] 5) Antimony trioxide, zinc borate, calcium hydroxyphosphate and ammonium polyphosphate were added to the reactor, and the mixture was stirred at 300 r / min for 10 minutes to obtain a mixed flame retardant component. The tin-bismuth alloy powder formed in the ball mill was transferred to the reactor, and the mixture was stirred for 30 minutes until the components were evenly mixed to obtain a reinforced mixture.

[0108] 6) Octylphenol polyoxyethylene ether and polyvinyl pyrrolidone are mixed according to a ratio, and the formed emulsion is added to the reinforced mixture in the reactor, and mixed at a speed of 300 r / min for 60 minutes. The emulsion fully disperses the solid particles of the modified tin powder and bismuth powder to form a flame retardant mixed slurry;

[0109] 7) Dry the mixed slurry to remove moisture. The drying temperature is controlled at 80°C and the drying time is 3 hours. After drying, the material is crushed and sieved to obtain a tin-bismuth-based high-efficiency flame retardant product with uniform particle size. The finished product is packed into a sealed container and stored in a dry and cool place for use.

[0110] The present invention also provides a non-metallic product for coal mines, which is manufactured based on a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products. The manufacturing method of the non-metallic product for coal mines is as follows: the prepared tin-bismuth-based high-efficiency flame retardant powder is uniformly added to 92% polystyrene (PS) at a mass ratio of 8%, and 8% of the tin-bismuth-based high-efficiency flame retardant and 92% of the polystyrene (PS) matrix material are weighed according to the mass ratio. The tin-bismuth-based high-efficiency flame retardant powder is uniformly added to polystyrene (PS); a high-speed mixer is used to fully mix at a speed of 2000 r / min for 20 minutes to fully mix the flame retardant and the matrix material. The uniformly mixed material is subjected to an extrusion process, extruded at 170°C, and the extrusion pressure is 90 MPa; after cooling, a non-metallic product for coal mines with excellent flame retardant properties is obtained.

[0111] Comparative Example 1

[0112] A tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, comprising the following raw materials in parts by weight:

[0113] 25 parts of bismuth powder; 7.5 parts of antimony trioxide; 7.5 parts of zinc borate; 3 parts of hydroxy calcium phosphate; 4.5 parts of ammonium polyphosphate; 2 parts of nano silicon dioxide; 3.5 parts of magnesium oxide; 15 parts of aluminum hydroxide; 0.75 parts of silane coupling agent; 0.3 parts of octylphenol polyoxyethylene ether, 0.4 parts of polyvinyl pyrrolidone. Among them, the tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines does not contain modified tin powder.

[0114] Comparative Example 2

[0115] A tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, comprising the following raw materials in parts by weight:

[0116] 50 parts of modified tin powder; 7.5 parts of antimony trioxide; 7.5 parts of zinc borate; 3 parts of calcium hydroxyphosphate; 4.5 parts of ammonium polyphosphate; 2 parts of nano silicon dioxide; 3.5 parts of magnesium oxide; 15 parts of aluminum hydroxide; 0.75 parts of silane coupling agent; 0.3 parts of octylphenol polyoxyethylene ether and 0.4 parts of polyvinyl pyrrolidone. Among them, the tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines does not contain bismuth powder.

[0117] Comparative Example 3

[0118] A tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, comprising the following raw materials in parts by weight:

[0119] 7.5 parts of antimony trioxide; 7.5 parts of zinc borate; 3 parts of hydroxy calcium phosphate; 4.5 parts of ammonium polyphosphate; 2 parts of nano silicon dioxide; 3.5 parts of magnesium oxide; 15 parts of aluminum hydroxide; 0.75 parts of silane coupling agent; 0.3 parts of octylphenol polyoxyethylene ether and 0.4 parts of polyvinyl pyrrolidone. Among them, the tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines does not contain modified tin powder and bismuth powder.

[0120] The preparation processes of Comparative Examples 1-3 are the same as those of Example 3.

[0121] Effect verification:

[0122] The tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products prepared in Examples 1-5 and the tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products prepared in Comparative Examples 1-3 were tested as follows:

[0123] (1) Flame retardant performance test

[0124] Test item: flame retardant performance.

[0125] Test method: The coal mine non-metallic products prepared in Examples 1-5 and Comparative Examples 1-3 were selected, and a horizontal combustion test was performed according to the ASTM D635 standard and a vertical combustion test was performed according to the UL 94 standard. The test results are as follows:

[0126] 1. Example 1-5: Passed UL 94 V-0 grade (self-extinguishing within 10 seconds, dripping is not flammable).

[0127] 2. Comparative Examples 1-3: Passed UL 94 V-2 grade (self-extinguishing within 30 seconds, dripping material burns).

[0128] (2) Thermal stability test

[0129] Test item: Thermal stability.

[0130] Test method: Select the coal mine non-metallic products prepared in Examples 1-5 and Comparative Examples 1-3, use a thermogravimetric analyzer (TGA), and heat from room temperature to 600°C at a heating rate of 10°C / min in a nitrogen atmosphere to measure the thermal degradation temperature and mass loss of the samples. The test results are as follows:

[0131] 1. Example 1-5: The initial thermal degradation temperature is above 280°C, and the mass loss rate is less than 30% at 500°C.

[0132] 2. Comparative Examples 1-3: The initial thermal degradation temperature is below 250°C, and the mass loss rate is greater than 50% at 500°C.

[0133] (3) Mechanical properties test

[0134] Test items: tensile strength, flexural strength.

[0135] Test method: The non-metallic products of coal mines prepared in Examples 1-5 and Comparative Examples 1-3 were selected, and tensile tests were performed according to ASTM D638 and bending tests were performed according to ASTM D790 using an electronic universal testing machine. The test results are as follows:

[0136] 1. Example 1-5: The tensile strength is above 30 MPa, and the bending strength is above 50 MPa.

[0137] 2. Comparative Examples 1-3: The tensile strength is below 25 MPa, and the flexural strength is below 40 MPa.

[0138] (4) Wear resistance test

[0139] Test item: wear resistance.

[0140] Test method: The non-metallic products of coal mines prepared in Examples 1-5 and Comparative Examples 1-3 were selected and tested using a Taber wear tester in accordance with ASTM D1044 standard. A CS-10 grinding wheel was used with a load of 500 g and a rotation number of 1000 revolutions. The mass loss of the samples was measured. The test result data is as follows:

[0141] 1. Example 1-5: The mass loss is less than 10 mg.

[0142] 2. Comparative Examples 1-3: The mass loss was greater than 20 mg.

[0143] (5) Anti-aging performance test

[0144] Test items: tensile strength, flexural strength.

[0145] Test method: The non-metallic products of coal mines prepared in Examples 1-5 and Comparative Examples 1-3 were selected and tested using a UV aging test box according to ASTM G154 standard. The samples were exposed to UV light (UVB-313 lamp) and the mechanical properties of the samples were measured after 500 hours of testing. The test results are as follows:

[0146] 1. Example 1-5: The tensile strength and flexural strength decreased by less than 10%.

[0147] 2. Comparative Examples 1-3: The tensile strength and flexural strength decreased by more than 20%.

[0148] The specific test results are shown in Table 1.

[0149] Table 1 Summary of test results of tin-bismuth-based high-efficiency flame retardants for non-metallic products in coal mines

[0150]

[0151] It can be seen from the above test results that the tin-bismuth-based high-efficiency flame retardants for coal mine non-metallic products prepared in Examples 1-5 are superior to the samples of Comparative Examples 1-3 in terms of flame retardancy, thermal stability, mechanical properties, wear resistance and anti-aging properties, verifying the excellent performance and practical application effect of the tin-bismuth-based high-efficiency flame retardants.

[0152] The tin-bismuth-based high-efficiency flame retardant of the present invention and its preparation method and application have the advantages of excellent flame retardant performance, high-efficiency smoke suppression, significant synergistic effect, environmental friendliness, etc., are suitable for wide application in non-metallic products in coal mines, improve the safety and reliability of coal mine production, and provide a new solution for fire protection technology.

[0153] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A tin-bismuth-based high-efficiency flame retardant for non-metallic products in coal mines, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of modified tin powder; 20-30 parts of bismuth powder; 5-10 parts of antimony trioxide; 5-10 parts of zinc borate; 2-4 parts of calcium hydroxyphosphate; 3-6 parts of ammonium polyphosphate; 1-3 parts of nano silicon dioxide; 2-5 parts of magnesium oxide; 10-20 parts of aluminum hydroxide; 0.5-1 part of silane coupling agent; Octylphenol polyoxyethylene ether 0.1-0.5 parts, polyvinyl pyrrolidone 0.2-0.6 parts; The modified tin powder is tin powder with aluminum oxide coated on the surface. The particle size of the modified tin powder is 10-50um, the thickness of the aluminum oxide coating layer is 100nm, and the apparent density is 2.0-2.5 g / cm³. The modified tin powder forms a uniform aluminum oxide coating layer on the surface of the tin powder through chemical vapor deposition; the particle size of the bismuth powder is 10-50um, and the apparent density is 9.8-10.2 g / cm³, used to combine with modified tin powder to form tin-bismuth alloy; the zinc borate is ultrafine zinc borate with a particle size of 50-100nm and a specific surface area of ​​30m² / g; the hydroxy calcium phosphate is a nano hydroxy calcium phosphate with a particle size of 20-50nm and a specific surface area of ​​60m² / g; the antimony trioxide has a particle size of 100nm to 1um and a specific surface area of ​​20m² / g; the ammonium polyphosphate has a particle size of 100-500nm, a density of 1.9g / cm³, and a degree of polymerization of the ammonium polyphosphate greater than 200; the particle sizes of the nano silicon dioxide, magnesium oxide and aluminum hydroxide are all 10-50nm, wherein the specific surface area of ​​the nano silicon dioxide is 200-400 m² / g, the specific surface area of ​​the magnesium oxide is 150 m² / g, and the specific surface area of ​​the aluminum hydroxide is 100 m² / g.

2. The tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products according to claim 1, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane.

3. The tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products according to claim 2, characterized in that: The polyvinyl pyrrolidone is K30 type polyvinyl pyrrolidone with a viscosity of 5-10 mPa.s and a density of 1.2 g / cm³. Vinyl pyrrolidone monomer and potassium persulfate are reacted by adding ethanol into a reaction container, the reaction temperature is controlled between 60-80°C, the reaction is uniformly stirred for 4-8 hours, and the polyvinyl pyrrolidone is separated.

4. A method for preparing a tin-bismuth-based high-efficiency flame retardant for coal mine non-metallic products according to any one of claims 1 to 3, characterized in that: Here are the steps: 1) Weigh modified tin powder, bismuth powder, antimony trioxide, zinc borate, calcium hydroxyphosphate, ammonium polyphosphate, nano silicon dioxide, magnesium oxide, aluminum hydroxide, silane coupling agent, octylphenol polyoxyethylene ether and polyvinyl pyrrolidone according to weight parts and set aside; 2) Activation treatment of bismuth powder: dissolving 20% ​​of the weighed silane coupling agent in anhydrous ethanol to prepare a 0.5-1% silane coupling agent solution; spreading the bismuth powder evenly, and spraying the silane coupling agent solution on the surface of the spread bismuth powder, placing the sprayed bismuth powder in an oven, and drying it at 80-100° C. for 1-2 hours to obtain bismuth powder activated by the silane coupling agent; 3) adding the modified tin powder and the activated bismuth powder into a ball mill according to a weight ratio for pre-mixing by ball milling to form a tin-bismuth alloy powder; 4) Add nano-silicon dioxide, magnesium oxide and aluminum hydroxide into the reactor, and slowly add the remaining amount of silane coupling agent, with a stirring speed of 200-250 r / min, a stirring time of 10-20 minutes, and a temperature of 25°C, so that the silane coupling agent fully reacts with the surface of nano-silicon dioxide, magnesium oxide and aluminum hydroxide to perform surface modification; 5) adding antimony trioxide, zinc borate, calcium hydroxyphosphate and ammonium polyphosphate to the reactor, stirring at 300-500 r / min for 5-10 minutes to obtain a mixed flame retardant component, and transferring the tin-bismuth alloy powder formed in the ball mill to the reactor, stirring for 15-30 minutes until the components are evenly mixed to obtain a reinforced mixture; 6) Octylphenol polyoxyethylene ether and polyvinyl pyrrolidone are mixed according to a ratio, and the formed emulsion is added to the reinforced mixture in the reactor, and mixed at a speed of 300-500 r / min for 30-60 minutes, so that the emulsion fully disperses the solid particles of the modified tin powder and bismuth powder to form a flame retardant mixed slurry; 7) Dry the mixed slurry to remove moisture, control the drying temperature at 60-80°C, and dry for 3-5 hours. After drying, crush and sieve the material to obtain a tin-bismuth-based high-efficiency flame retardant product with uniform particle size, put it into a sealed container, and store it in a dry and cool place for use.

5. A non-metallic product for coal mines, manufactured using the tin-bismuth-based high-efficiency flame retardant for non-metallic products for coal mines as claimed in any one of claims 1 to 3, characterized in that: The manufacturing method of the coal mine non-metallic product is: The prepared tin-bismuth-based high-efficiency flame retardant powder is evenly added to the base material at a mass ratio of 5-10%, the flame retardant and the base material are fully mixed by a high-speed mixer, and the mixed material is processed into the required coal mine non-metallic products by injection molding, extrusion or compression molding.

Citation Information

Patent Citations

  • High-abrasion-resistance, halogen-free and flame-retardant insulation material for thin-wall locomotive cable

    CN105820558A

  • Flame retardant for polyvinyl chloride wall decoration film material and preparation method of flame retardant

    CN106832421A